Giant Cell Arteritis Presenting With Ocular Symptoms: Clinical Characteristics and Multimodal Imaging in a Chinese Case Series - Chen, Qian; Chen, Weimin; Feng, Chaoyi; Gong, Deshan; Zhang, Jiong; Bi, Yingwen; Sun, Ping; Sun, Xinghuai; Tian, Guohong (Frontiers in Medicine, 2022)
Purpose: To evaluate demographic and clinical characteristics of a Chinese population with giant cell arteritis using multimodal imaging focusing on ophthalmic examinations. Design: Retrospective observational case series Methods: In the neuro-ophthalmology division of the Eye, Ear, Nose, and Throat Hospital, Shanghai, we evaluated the demographic and clinical characteristics of patients diagnosed with giant cell arteritis between January 2016 and June 2021. Results of routine ophthalmic examinations including fundus examination, optical coherence tomography, color duplex ultrasonography of ocular and superficial temporal arteries, orbital magnetic resonance imaging, and superficial temporal artery biopsy were evaluated. Results: A total of 15 patients (22 eyes; ten male and five female) were evaluated with a mean age of 77.0±8.5 years. Among them, seven had bilateral involvement that occurred simultaneously or sequentially. Twelve patients presented with arteritic anterior ischemic optic neuropathy, two with arteritic anterior ischemic optic neuropathy combined with cilioretinal artery occlusion, and one with cotton-wool spots. In acute stages of optic neuropathy and retinopathy, optical coherence tomography revealed optic disc edema, thickening of the inner retinal nerve fiber layer and ganglion cell layer, and loss of layer structure. In late stages, optical coherence tomography revealed diffuse atrophy of the inner retina. The “halo” sign was observed in 12 patients in the superficial temporal artery ultrasound, and seven out of eight patients who underwent biopsy demonstrated classic giant cell arteritis pathological changes. Most patients having poor visual acuity but ability to perceive light; 10/22 eyes had permanent vision loss. Conclusions: Although rare in Asians, giant cell arteritis may be underdiagnosed among elderly Chinese patients presenting with anterior ischemic optic neuropathy. Non-invasive superficial temporal artery ultrasound detecting inflammatory thickening of the intima as the “halo” sign combined with routine elevated erythrocyte sedimentation rate and C-reactive protein may be helpful in diagnosing patients with a high probability of having giant cell arteritis.